1984
DOI: 10.1042/bj2210915
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an adenosine-receptor antagonist on insulin-resistance in soleus muscle from obese Zucker rats

Abstract: The decreased sensitivity of glycolysis to insulin seen in isolated soleus muscles from genetically obese Zucker rats was abolished by addition of the adenosine-receptor antagonist 8-phenyltheophylline to the incubation medium; 8-phenyltheophylline had no effect on the sensitivity of glycogen synthesis to insulin. These findings suggest that changes in the sensitivity of glucose utilization by muscles of genetically obese rats may be explained, in part, by a modification in either the concentration of adenosin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
33
0

Year Published

1987
1987
2013
2013

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 14 publications
2
33
0
Order By: Relevance
“…Increased AMP concentration might lead to extra adenosine formation (affecting glucose uptake) (11)(12)(13) as well as activation of ATP synthesis mediated by AMP-activated protein kinase (47,48). The latter, however, is hindered by inhibition of adenine nucleotide translocator by long-chain fatty acyl-CoA esters.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased AMP concentration might lead to extra adenosine formation (affecting glucose uptake) (11)(12)(13) as well as activation of ATP synthesis mediated by AMP-activated protein kinase (47,48). The latter, however, is hindered by inhibition of adenine nucleotide translocator by long-chain fatty acyl-CoA esters.…”
Section: Resultsmentioning
confidence: 99%
“…The increase in AMP concentration should promote formation of adenosine, which in turn was reported to have both inhibitory and stimulatory effects on insulin-dependent glucose uptake (11)(12)(13). It was hypothesized that an increased extracellular adenosine concentration could explain such pathophysiological features of type 2 diabetes as elevated levels of uric acid, increased sympathetic activity, and expansion of extracellular volume (9).…”
mentioning
confidence: 99%
“…Furthermore, the stimulation of the rate of glycogen synthesis by insulin in the muscle can be metabolically independent of the effect of insulin on glucose transport, since glycogen synthase catalyses a flux-generating step [45]. Thus, adenosine receptor antagonists have previously been shown to increase the sensitivity of glucose transport and glycolysis to insulin without affecting the sensitivity of glycogen synthesis [46].…”
Section: Resultsmentioning
confidence: 99%
“…In the periphery, interstitial adenosine may be involved in insulin-mediated glucose metabolism, although controversy exists as to whether adenosine exerts opposing effects in adipose tissue and skeletal muscle. Some studies have reported adenosine to increase insulin-mediated glucose metabolism in adipose tissue (5,31) and to decrease metabolism in skeletal muscle (32). Others have recorded decreased skeletal muscle glucose uptake with degradation or blocking of adenosine (33,34), indicating uniform effects of adenosine on (insulin-mediated) glucose metabolism in fat and muscle.…”
mentioning
confidence: 99%